Investigação teórica de propriedades estruturais e físico-químicas de complexos de lantanídeos - Daniel Mungo Brasil (2023)
Computational chemistry uses computational resources to solve highly complex mathematical equations to give information about the physicochemical properties of multielectronic systems. These equations originated from classical mechanics, a method called molecular mechanics, or from quantum mechanics, ab initio methods and density functional theory (DFT). The latter was chosen to develop the present work. DFT was developed for calculations of fundamental state properties and for those calculations involving excited states one uses its extension, the time-dependent density functional theory (TD-DFT). These computational techniques allow us to improve our understanding of the structure-property relationship, as in the case of the lanthanide complexes discussed in the present work. Lanthanide complexes have several applications, from drugs to light-converting devices, therefore there is great interest in such materials. In this work, five lanthanide complexes were studied, one formed by the gadolinium(III) ion with the usnate ligand, and two of them formed by the 3,5-dimethoxy benzoate monocarboxylate ligand with the lanthanum(III) and cerium(III) ions, a europium(III) complex with phenanthroline and 2-thenoyltrifluoroacetone and a similar complex but silylated phenanthroline. The calculations were performed using the Gaussian16 and ORCA 4.0.1 programs, the B3LYP exchange-correlation hybrid functional, and the def2-SVP basis set for light atoms. For lanthanides, the def2-TZVP basis set was used with the effective core potential. Geometry optimization and calculations for obtaining the infrared spectra and absorption of the ultraviolet-visible region were carried out for all complexes. Frontier molecular orbital diagrams were also obtained to analyze and assign the electronic spectrum. For the five studied compounds, the theoretical infrared spectra agree with the experimental spectra, the absorption spectra present a small displacement compared to the experimental spectra, but the structure of the bands matches. The theoretical data showed good agreement with the experimental data, proving that the computational methods can be used to understand the geometry and electronic structure and elucidate the absorption spectra.